AB0009 Tnf alpha as a marker of articular involvement in patients infected with hiv. (1st June 2001) - Bagnato, GG; Romano, C; Arrigo, C; Chirico, G
Abstract : Background: In the last years great attention was given to the problems correlated to Hiv infection. The clinical rheumatologic manifestations correlated to Hiv infection generally are olygo-polyarthritis, polyarthritis or Reiter Syndrome. The Hiv arthritis usually olygoarticular and asymmetric, involves the big articulations and it isn't correlate to Hla B27 aplotype. Some studies demonstrated an articular involvement in about 30% of the patients. Seems that the particular problems are correlated with a disregulation of the immune system with a sovraexpression of some pro-inflammatory cytokines. Objectives: Aim of this study was to evaluate the prevalence of rheumatologic manifestations in patients with Hiv infection and to evaluate if there was a correlation between articular involvement and sovraexpression of TNF alpha that is such important in articular omeostasis. Methods: We selected 46 patients with Hiv infetion, mean age 39 (22–59), 10 healthy subjects and 10 with rheumatoid arthritis as negative and positive controls. At the beginning of this study we did an articular evaluation with a questionnaire with 10 items regarding rheumatological problems in all the Hiv+ patients. Results: We found rheumatologic manifestations in 11(24%) and the most common was the presence of diffuse polyartralgias. Seric TNF alpha levels were increased in the Hiv group with articular involvement and was normal in those without articular involvement (p = 0, 02) but there weren't statistical differences between the 2 groups for CD4 count and viral load. Conclusion: TNF alpha seems to be a clear index of articular involvement in patients with HIV infection but doesn't seems to be correlated to viral load and progression of disease.